If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 272 = 3Y + X + 32 Reorder the terms: 272 = 32 + X + 3Y Solving 272 = 32 + X + 3Y Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1X' to each side of the equation. 272 + -1X = 32 + X + -1X + 3Y Combine like terms: X + -1X = 0 272 + -1X = 32 + 0 + 3Y 272 + -1X = 32 + 3Y Add '-272' to each side of the equation. 272 + -272 + -1X = 32 + -272 + 3Y Combine like terms: 272 + -272 = 0 0 + -1X = 32 + -272 + 3Y -1X = 32 + -272 + 3Y Combine like terms: 32 + -272 = -240 -1X = -240 + 3Y Divide each side by '-1'. X = 240 + -3Y Simplifying X = 240 + -3Y
| 3y+12-y=10 | | -8(s+3)=-44 | | -5j-1=1+11j-15j | | X^2+11x-48=0 | | 12c-13=19+14c | | 18h-14=19+20h+5 | | 5(x+6)+3(-x+8)=6 | | 2y=y/10 | | -10d-2=-8d+10-5d | | 5x+2+1=11 | | -2p+10-8p=3-9p | | f+8=-8-f | | 2x^3+6x^2+1=0 | | 7g=9 | | 5(x+6)+3(-x+8)=36 | | 272=3x+y | | 7+5f=19+2f | | 12+x-5=7*4-10 | | 5x-3(x-4)=-9+4x+11 | | 3(x+35)+4(x+35)=7 | | 24=-2(x-9) | | 3(5x-52)=2(x+26) | | 3x-24+3x+9=97-13x | | 4(5x+85)=3(x+34) | | -4x+9=-2x+17 | | 50=5p+5 | | 3-6x=9-9x | | -2.1x+4.7=y | | 5(v-8)=-10+5v | | 6z-1=4z+3 | | S=5t+5t^2 | | 11.2+3y=20.2 |